2015
DOI: 10.3892/mmr.2015.4715
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin enhances the antitumor effect of ABT-737 via activation of the ROS-ASK1-JNK pathway in hepatocellular carcinoma cells

Abstract: At present, the therapeutic treatment strategies for patients with hepatocellular carcinoma (HCC) remain unsatisfactory, and novel methods are urgently required to treat this disease. Members of the B cell lymphoma (Bcl)-2 family are anti-apoptotic proteins, which are commonly expressed at high levels in certain HCC tissues and positively correlate with the treatment resistance of patients with HCC. ABT-737, an inhibitor of Bcl-2 anti-apoptotic proteins, has been demonstrated to exhibit potent antitumor effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…Synergistic Effect of DOX with ABT-199, ABT-263, or ABT-737. In previous reports, ABT-737 and chemotherapeutic agents had the synergistic effect during HCC treatment [32,33]. However, there was not a report of ABT-263 and ABT-199 in the combinational chemotherapy of HCC.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Synergistic Effect of DOX with ABT-199, ABT-263, or ABT-737. In previous reports, ABT-737 and chemotherapeutic agents had the synergistic effect during HCC treatment [32,33]. However, there was not a report of ABT-263 and ABT-199 in the combinational chemotherapy of HCC.…”
Section: Resultsmentioning
confidence: 94%
“…And it also depends on the induction of apoptosis. Moreover, they indicated that activation of the ROS-ASK1-c-Jun N-terminal kinase pathway should be an important factor of the synergy in the combination [33]. Thus, ABT-199, ABT-263, and ABT-737 have potential to be used for screening of more effective drug combinations in treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…ASK1 acts as a serine/threonine protein kinase and participates in multiple biologic processes [43]. Upon accumulation of ROS in cancer cells, ASK1 is activated, leading to apoptotic cell death [25,26,44]. Therefore, ASK1 is a key intermediate in the ROS-dependent pathway of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We thus demonstrated the importance of the ROS/ASK1 pathway in cytotoxicity of anti-miR-20a and cisplatin co-treatment in CRC. As JNK is an important substrate of ASK1 [26], we next investigated the role of JNK in anti-miR-20a-enhanced cell death. We found that addition of the JNK specific inhibitor SP600125 [27] significantly protected the LoVo cells from cisplatin and anti-miR-20a co-treatment (Fig.…”
Section: Anti-mir-20a Promotes Cisplatin-induced Cytotoxicity In Crc mentioning
confidence: 99%
“…Leukemia is one of the leading types of cancer across the globe. In 2014, data collected from United States revealed that total number of leukemia patients was 52,380 in which 30,100 patients were male while 22,280 were females. The number of deaths was as high as 24,090 in which 14,040 were females and 10,050 were males [14].…”
Section: Introductionmentioning
confidence: 99%